2022
DOI: 10.3389/fimmu.2022.931194
|View full text |Cite
|
Sign up to set email alerts
|

MDA5 signaling induces type 1 IFN- and IL-1-dependent lung vascular permeability which protects mice from opportunistic fungal infection

Abstract: Lungs balance threat from primary viral infection, secondary infection, and inflammatory damage. Severe pulmonary inflammation induces vascular permeability, edema, and organ dysfunction. We previously demonstrated that poly(I:C) (pICLC) induced type 1 interferon (t1IFN) protected mice from Cryptococcus gattii (Cg) via local iron restriction. Here we show pICLC increased serum protein and intravenously injected FITC-dextran in the lung airspace suggesting pICLC induces vascular permeability. Interestingly, pIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…A study by Oliveira et al [48] suggested that IAV infection induces the secretion of type 1 interferons (IFN-a and IFN-b), which are considered key cytokines in the host defence against the fungus Cryptococcus gattii. Moreover, Flesch et al [49] and Davis et al [50] reported that IFN-c promoted macrophage phagocytosis and killing of fungi. C. gattii is an emerging and still poorly understood pathogen, and inflammatory responses resulting in reduced IFNc may be responsible for increased susceptibility to secondary C. gattii infection.…”
Section: Superinfection Of Fungi and Virusesmentioning
confidence: 99%
See 3 more Smart Citations
“…A study by Oliveira et al [48] suggested that IAV infection induces the secretion of type 1 interferons (IFN-a and IFN-b), which are considered key cytokines in the host defence against the fungus Cryptococcus gattii. Moreover, Flesch et al [49] and Davis et al [50] reported that IFN-c promoted macrophage phagocytosis and killing of fungi. C. gattii is an emerging and still poorly understood pathogen, and inflammatory responses resulting in reduced IFNc may be responsible for increased susceptibility to secondary C. gattii infection.…”
Section: Superinfection Of Fungi and Virusesmentioning
confidence: 99%
“…As occurs during IAV infection, during infection with influenza B virus, the bronchial ciliated epithelium is stripped and local haemorrhage and necrosis may occur, which can cause dual infection with bacteria or fungi. Additionally, the loss of ciliary function of the bronchial tree during acute influenza B virus infection may predispose patients to invasive fungal infections [49][50][51].…”
Section: Superinfection Of Fungi and Virusesmentioning
confidence: 99%
See 2 more Smart Citations